Analysis on anti‐wear mechanism of bionic non‐smooth surface based on discrete phase model. Issue 13 (21st November 2018) - Gao, Dianrong; Liu, Jingcheng; Xu, Xuehan; Zhang, Zongyi
Abstract : In order to study the lubrication and anti‐wear mechanism of the pit‐type bionic non‐smooth surface used in the low‐speed and high‐torque seawater hydraulic motor valve plate pair, the discrete phase models of the four pits are simulated under different working conditions. In this study, the trajectories of different diameters particles in the hemispherical pits are analysed, which can reflect the movement of different sizes and masses wear debris in the pits. The discrete phase concentration distributions of the four‐kind pits, hemispherical pits, cylindrical pits, four‐prism pits and tri‐prism pits, are simulation under the same working conditions, which reflects the effect of pit geometry on the movement of wear debris. The discrete phase concentration distributions of four pits moving at different rotation speeds and different rotation radii are calculated, which indicates that the rotation speed of the motor and the distribution of pits on the valve plate will affect the ability of the pit to store wear debris.